Analysis of FNAC indication in thyroid nodules assessed as low risk according to various TIRADSs - Pierpaolo Trimboli; Petra Makovac; Amos Colombo; Lorenzo Ruinelli; Chiara Dobrinja; Lorenzo Scappaticcio; Andrea Leoncini (European Thyroid Journal)
Background: Thyroid nodule (TN) is a common entity, and TNs assessed by Thyroid Imaging and Reporting Data Systems (TIRADSs) as low-risk lesions (TIRADS 3) can significantly impact the rate of unnecessary biopsy (UN-FNAC). This study reviewed a consecutive series of patients undergoing surgery to analyze TNs assessed as TIRADS 3. Methods: Thyroid surgeries performed from January 2019 to August 2024 were reviewed. Patients with preoperative thyroid ultrasound were selected, and TNs were classified according to American College of Radiology (ACR), European Thyroid Association (EU), and Korean (K) TIRADS. Cases assessed as TIRADS 3 were finally included. Histology was the reference standard to calculate the rate of UN-FNAC. Results: The study series included 284 TNs assessed as TIRADS 3. The risk of malignancy was 8.7% in ACR-, 10.7% in EU-, and 10.1% in K-TIRADS, higher than expected. The frequency of TNs with indication for biopsy according to K-TIRADS (66.7%) was significantly (P = 0.003) higher than ACR-TIRADS (46.7%), with an intermediate value of EU-TIRADS (56.5%). The percentage of cancers with indication for biopsy according to ACR-, EU-, and K-TIRADS was 25%, 50%, and 50%, respectively. The overall rate of UN-FNAC was 95.3% in ACR-TIRADS, 90.3% in EU-TIRADS, and 92.4% in K-TIRADS. Conclusion: How to save on UN-FNACs in low-risk TNs is challenging. Although ACR-TIRADS can be effective in reducing the total number of biopsies, the rate of UN-FNAC remains significant. Alternative strategies should be developed.